Correspondence of Pubertal Neuroendocrine and Tanner Stage Changes in Boys and Associations With Substance Use. Issue 6 (31st May 2018) - Marceau, Kristine; Kirisci, Levent; Tarter, Ralph E.
Abstract : This study examined correspondence between timing (onset) and tempo (rate) of sexual maturation prospectively (average ages 11–16 years) measured by gonadal hormones and secondary sex characteristics (Tanner stage) using dual‐process models, and associations of these measures with substance use (SU) involvement in boys at age 16 years ( N  = 534, 77.5% White/22.5% Non‐White). All measures of timing were highly associated. Early Tanner stage timing often predicted slower increases in gonadal steroids, but not the reverse; patterns varied by ethnicity. Hormone and Tanner stage measures were similar earlier in development but diverged later in development. In White boys only, early timing of the pubertal rise in testosterone was associated with increased SU involvement, suggesting a physiological rather than psychosocial mechanism of association.